2015
DOI: 10.1161/hypertensionaha.114.05003
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure in Untreated and Treated Hypertensive Patients at High Altitude

Abstract: A cute exposure to high-altitude hypoxia induces important changes in cardiovascular regulation, [1][2][3][4] including an increase in blood pressure (BP) and heart rate (HR). 2,[5][6][7][8] Millions of subjects travel for relatively short periods of time to high altitude either for work or for leisure including many affected by hypertension 9 in whom the pressor effect of high altitude may be relevant. Limited information is available, however, on the acute BP effects of high altitude in hypertensive subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 37 publications
6
53
0
4
Order By: Relevance
“…Moreover, it is unclear whether antihypertensive therapy would just result in a downward shift of BP levels, or if it might also reduce the rate of BP increase occurring during exercise, thus modulating BP hyperreactivity. These questions were not addressed in our previous article,1, 2, 3 and discordant answers were found on the basis of the results of the few studies that addressed these issues up to now 7, 8, 9…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Moreover, it is unclear whether antihypertensive therapy would just result in a downward shift of BP levels, or if it might also reduce the rate of BP increase occurring during exercise, thus modulating BP hyperreactivity. These questions were not addressed in our previous article,1, 2, 3 and discordant answers were found on the basis of the results of the few studies that addressed these issues up to now 7, 8, 9…”
Section: Introductionmentioning
confidence: 74%
“…One hundred individuals with grade I essential hypertension (conventional systolic BP 140–159 mm Hg or conventional diastolic BP 90–99 mm Hg and mean daytime systolic BP ≥135 and <150 mm Hg and/or mean daytime diastolic BP ≥85 and <95 mm Hg) and no significant comorbidities, either untreated or having previously stopped antihypertensive therapy for 4 weeks, were enrolled in the frame of the HIGHCARE‐ANDES study 1. All subjects were sea‐level residents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 We have previously shown that during short exposure to lower altitudes (≈3400 m) when RAAS at least partly retains its activity, the angiotensin antagonist telmisartan remains effective in BP lowering both in normotensive 24 and in hypertensive subjects. 41 Conversely, telmisartan lost its ability to reduce BP during prolonged exposure to very HA, likely because of the above reported suppression of RAAS. 24 In line with these findings, we also observed no difference in parameters reflecting viscoelastic properties of large arteries, such as PWV and other variables obtained from pulse wave analysis, including subendocardial oxygen supply and demand ratio, between telmisartan-treated and untreated subjects at any altitude.…”
Section: Raas and Hemodynamic Changes At Hamentioning
confidence: 99%
“…In the HIGHCARE-Andes Lowlanders Study, BP changes in response to high altitude exposure and the BP effects of antihypertensive combination treatment with an angiotensin II receptor blocker and a calcium channel blocker (ARB/ CCB) both at sea level and during high altitude exposure were assessed in a group of patients with mild hypertension (Bilo et al, 2015).…”
Section: Effects Of Aging On Blood Pressure and Its Regulation At Higmentioning
confidence: 99%